The model of the secular state and the politics of secularism in Kazakhstan: modern challenges - Shapoval, Yu V. (Relihijna svoboda, 2020)
The article focuses on the evolution of the secularism policy pursued in Kazakhstan since independence. The liberal Law "On Freedom of Conscience and Religious Associations", adopted by one of the first in January 1992, is defined as the initial stage. The next stage is the transition from a soft border between religiosity and secularism to more stringent state regulation. Such a turn for the secularism model in Kazakhstan was noted in 2011. At this stage in the evolution of the politics of secularism, a new Law of the Republic of Kazakhstan (RK) on Religious Activities and Religious Associations was adopted. At this time, the problem of religious radicalization and religious extremism is becoming more relevant. Even before the 2000s, religious radicalism in Kazakhstan was predominantly imported, and in 2003-2004 there were signs of the emergence of the so-called "homegrown" terrorism. The situation was aggravated after the move of young people, citizens of Kazakhstan to the war zone in Syria by their entry into the ranks of militants, under the auspices of the "Hijra to the Islamic State." As a definite reaction, the State Program on Combating Religious Extremism and Terrorism in the Republic of Kazakhstan for 2013-2017 was adopted. As part of the implementation of this program, work has been launched to prevent the involvement of people in radical religious ideology. However, measures taken by the state were insufficient and ineffective. A particularly active departure of citizens of Kazakhstan to the "Islamic State" took place from 2014 to 2016. Therefore, the state faced an urgent need to rethink the factors of radicalization. As a result of operations Zhusan - 1, Zhusan - 2, Zhusan - 3, women with children from Syria were returned to Kazakhstan, which we define as another challenge to the secularism model in Kazakhstan. He forces to rethink all past experience of secularism, with the aim of finding a place for these women in a secular state. The article identifies several categories of returning women, examines the problems associated with the rehabilitation of these women and their re-socialization, analyzes the experience of Kazakhstan in this area.